Using information technology to leverage transport and logistics service operations in the supply chain: an empirical assessment of the interrelation between technology and operations management. (19th April 2004) - van Hoek, Remko I.
Based upon existing work, a synergistic relation between technology and operations management can be assumed. This paper uses a specific focus area to empirically validate this assumption. Within the field of third party logistics operations in the supply chain, technology can be expected to be a critical factor in achieving the often-targeted expansion of service offerings. The empirical research presented in this paper goes beyond existing material in this field, which remains mostly conceptual, qualitative or descriptive, by targeting statistical generalisation, using findings from a multi-annual survey of transport and logistics service operations in the supply chain. Findings show that existing operational arrangements of transport and logistics service providers mostly remain limited to traditional transport and warehouse services but that technology proves an answer to achieving the targeted expansion of third party operations. Case studies of three innovative service providers are used to develop insights into how technology impacts operational relations in the supply chain and how technology can leverage operations management in a synergistic manner.